Answer:
x = 1
y = -4
Explanation:
You can use 2 methods to solve this, substitution or elimination.
Elimination:
You want to try and get rid of one variable in the pair of equations.
We add them together since y and -y cancel each other out when added.
Now, we have a much simpler equation.
4x - y = 8
+ 6x + y = 2
------------------
10x = 10
x = 1
Now, you can just plug it back in to one of the equations to get y.
(4 x 1) - y = 8
4 - y = 8
y = -4
Substitution:
You can also try and change the equation so that there is only one variable by setting the other equation equal to a variable.
This one is easier to do:
6x + y = 2
y = -6x + 2
Now, plug it into the first equation replacing y, since they are equal, and solve:
4x - y = 8
4x - (-6x + 2) = 8
4x + 6x - 2 = 8
10x = 10
x = 1
Now, you can just plug it back in to one of the equations to get y.
6x + y = 2
(6 x 1) + y = 2
6 + y = 2
y = -4
:)